Community-Based Screening Programs In Public Healthcare: A Multidisciplinary Model Integrating Nursing, Radiology, Laboratory Services, Healthcare Security ,Social Workers, And Emergency Medical Services (EMS) (The Review of Diabetic Studies, 2024)
Community-based screening programs are central to modern public healthcare strategies aimed at early disease detection, prevention, and reduction of health inequities. As the burden of chronic diseases, infectious threats, and population vulnerability increases, isolated screening approaches are insufficient to address complex clinical, social, and security challenges. This narrative review examines a multidisciplinary model for community-based screening that integrates nursing, radiology, laboratory services, healthcare security, social work, and emergency medical services (EMS). Drawing on public health, clinical, and systems-based evidence, the review highlights coordinated workflows, data integration, risk stratification, referral pathways, and emergency preparedness. Emphasis is placed on how interprofessional collaboration enhances screening effectiveness, patient safety, and continuity of care while strengthening health system resilience.